The Psychology of Coronavirus Behavioral Health Mindset, Vaccination Receptivity, Customer Orientation and Community Public Service - Cunningham, Michael R.; Druen, Perri B.; Logsdon, M. Cynthia; Dreschler, Brian W.; Barbee, Anita P.; Carrico, Ruth L.; Billings, Steven W.; Jones, John W. (Frontiers in Psychology, 2022)
Three studies were conducted to explore the psychological determinants of COVID-deterrent behaviors. In Study 1, using data collected and analyzed both before and after the release of COVID-19 vaccines, mask-wearing, other preventative behaviors like social distancing, and vaccination intentions were positively related to assessments of the Coronavirus Behavioral Health Mindset (CVBHM); belief in the credibility of science; progressive political orientation; less use of repressive and more use of sensitization coping; and the attribution of COVID-19 safety to effort rather than ability, powerful forces, fate or luck. In Study 2, favorable COVID-19 vaccination intentions were related to greater willingness to work, lower emotional distress, and greater customer service mindset. Study 3 examined the personality and motives of individuals who volunteered to help deliver COVID-19 inoculations to the local community. The vaccine-giving volunteers, especially those with prosocial motives, had high CVBHM scores, belief in the credibility of science, low use of repressive coping, greater attribution of COVID-19 protection to effort, low likelihood of voting Republican, were older, and had more education than others. The majority of public health volunteers expressed prosocial motives to help people or join a cause (60.7%), but many (39.3%) expressed the personal motives of getting the COVID-19 vaccination for themselves, conveying a public image of compassion, or structuring time. Based on the three research studies, a COVID-19 Mindset Hierarchy model is proposed to integrate the results.